On the Jesuit-Maronite Provenance of Lebanon's Criminalization of Homosexuality - Strenski, Ivan (Journal of law and religion, 2020)
Article 534 of the Lebanese Penal Code, effectively, criminalizes homosexual practices. Most commentators have claimed that its existence in modern Lebanon is a "colonial relic," specifically of the French Mandate, 1920-1946. But since 1791, French penal codes have not criminalized same-sex relations. I argue, instead, that Article 534 was the product of native religious, legal, and moral thinking among the Maronites, reinforced by the Thomistic and post-Tridentine moral theology taught in Lebanon by the Jesuit missions. Thomistic and post-Tridentine moral theology classified same-sex relations as worthy of condemnation as "unnatural acts" - the same language used in Article 534. Therefore, as a product of Lebanese political and religious sectarianism, Article 534 is a specific case of a congenial collaboration of Jesuit moral theology and a conservative Maronite ethical and legal koine.